Small but Important Riots : The Cavalry Battles of Aldie, Middleburg, and Upperville - O'Neill, Robert F. (Book collections on Project MUSE., 2023)
"June 1863. The American Civil War was two years old, and the U.S. Army in Virginia was in chaos. Reeling after the recent defeat at Chancellorsville, the Federals, especially the Cavalry Corps, scrambled to regroup. Confederate general Robert E. Lee seized the moment to launch a second invasion of the North. As Lee slipped away, frantic Federal leaders asked, "Where are the Rebels?" At this critical moment, the much-maligned Federal cavalry stepped to center stage. Small but Important Riots is a tactical study of fighting from June 17 to 22, 1863, at Aldie, Middleburg, and Upperville, placed within the strategic context of the Gettysburg campaign. It is based on Robert O'Neill's thirty years of research and access to previously unpublished documents, which reveal startling new information. Since the fighting in Loudoun Valley of Virginia ended in June 1863, one perspective has prevailed-that Brigadier General Alfred Pleasonton, who commanded the Cavalry Corps, Army of the Potomac, disobeyed orders. According to published records, Pleasonton's superiors, including President Abraham Lincoln, Secretary of War Edwin Stanton, and army commander Joseph Hooker, ordered Pleasonton to search for General Robert E. Lee's Army of Northern Virginia during a critical stage of the Gettysburg campaign, and Pleasonton had ignored their orders. Recently discovered documents-discussed in this book-prove otherwise. "--